(untitled) (Iraqi Journal of Civil Engineering, 2012)
In this paper an analytical approximate solution for large flexural deformations, shear deformations and shear stresses of a bimodular uniformly loaded simply supported beam has been developed. Verification for the solution has been performed using FEM analysis with ANSYS. The results of the program were very close the results of the analytical solution presented in this paper.